Ruang Lingkup PAI Kontemporer bagi Pembelajaran Mahasiswa PPG - Kurniyadi, Mahmud Darul; Amin, Ahmad Yasir Al; Azharnurachman, Azharnurachman; Budiyono, Slamet (Lembaga Yasin AlSys, 2024)
Contemporary Islamic Education (PAI) plays a pivotal role in shaping the character, morality, and spirituality of individuals, particularly within the learning context for students of the Professional Teacher Education Program (PPG). In the contemporary era marked by globalization dynamics, technological advancements, and cultural pluralism, it is crucial for PPG students to comprehend and apply Islamic concepts within the evolving zeitgeist. The scope of contemporary PAI for PPG students encompasses various aspects, ranging from understanding the Quran and Hadith in modern life contexts to the utilization of technology in religious education. Additionally, topics such as Islamic ethics, character education, and Islamic-based classroom management are pivotal focuses in nurturing quality teaching professionalism. This abstract aims to provide a comprehensive overview of the contemporary PAI scope for PPG students and the significance of integrating Islamic values with the challenges and opportunities posed in modern education. Through a holistic and innovative approach, it is envisaged that PPG students can become agents of change, capable of inspiring future generations with relevant and inclusive Islamic values.